Agriculture: science and technology safeguard sustainability. Issue 3 (16th March 2019) - Jia, Hepeng
Abstract: China has traditionally placed tremendous importance on agricultural research. Meanwhile, in recent years, sustainable agriculture has been increasingly highlighted in both policy agenda and the capital market. However, while terms like environmental friendliness, low carbon, organic and green agriculture have become buzzwords in the media, few meaningful discussions have been raised to examine the relationship between science and technology (S&T) development and sustainable agriculture. What's more, some environmentalists stress that sustainable agriculture should abandon modern agriculture's heavy reliance on science and industrialization, making the link between agricultural S&T and sustainable agriculture seem problematic. What is the truth? If S&T are to play an important role in advancing sustainable agriculture, what is the current status of the field? What factors have caused the sustainable development of agriculture in China? At an online forum organized by the National Science Review ( NSR ), Hepeng Jia, commissioned by NSR executive editor-in-chief Mu-ming Poo, asked four scientists in the field to examine the dynamic relationship between sustainable agriculture and agricultural S&T in the Chinese context. Jikun Huang Agricultural economist at Peking University, Beijing, China Xiaofeng Luo Agricultural economist at Huazhong Agricultural University, Wuhan, China Jianzhong Yan Agricultural and environmental scientist at Southwest University, Chongqing, China Yulong Yin Veterinary scientist at Institute of Subtropical Agriculture, Chinese Academy of Sciences, Changsha, China Hepeng Jia (Chair) Science communication scholar at Cornell University, Ithaca, NY, USA